Non Coplanar Versus Coplanar VMAT Techniques for Pituitary Adenoma Radiotherapy - AL Hachami, Wisam Najm Abdullah (Universitas Muhammadiyah Sidoarjo, 2025)
This paper aims to investigate the dosimetric performance of two volumes of interest (VOIs) treated using coplanar as well as noncoplanar VMAT (volumetricmodulated arc therapy) in pituitary adenoma treatment. Fifteen patient cases were retrospectively studied with coplanar and noncoplanar VMAT plans generated. Dosimetric analysis concentrated on planning target volume (PTV) coverage and OAR sparing. The average dose to the PTV was 50.17Gy in coplanar plans and 50.20Gy in noncoplanar plans, demonstrating similar PTV coverage. Nevertheless, noncoplanar VMAT appeared to have a better conformity, with D95% achieving a maximum of 98.71% versus a maximum of 97.78% for coplanar. In OAR sparing, noncoplanar VMAT resulted in a significant decrease in the mean dose delivered to the right eye (8.56Gy vs 14.27Gy) and left eye (10.33Gy vs 12.32Gy). The mean dosimetric exposure was also lower in the left optic nerve for noncoplanar plans (26.57 vs 28.95). Notwithstanding, the highest brainstem dose increased marginally in noncoplanar plans (53.88 Gy versus 52.20 Gy); however, all dosimetric factors values still fell well within acceptable clinical constraints. These results indicated that noncoplanar VMAT techniques provide greater OAR-sparing capability with similar target dose coverage, which may support their clinical application for centrally located intracranial tumors, such as pituitary adenomas. Highlights: The prevalence of irritable bowel syndrome among Iraqi university students was 27.5%, with a higher rate in females than males. A significant association was found between IBS and anxiety, suggesting psychological factors play a major role. Lifestyle factors, including dietary habits and stress, were identified as key contributors to IBS prevalence